2017
DOI: 10.1016/j.devcel.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a Snf1-Mec1-Atg1 Module on Mitochondria Governs Energy Deprivation-Induced Autophagy by Regulating Mitochondrial Respiration

Abstract: Autophagy is essential for maintaining glucose homeostasis, but the mechanism by which energy deprivation activates autophagy is not fully understood. We show that Mec1/ATR, a member of the DNA damage response pathway, is essential for glucose starvation-induced autophagy. Mec1, Atg13, Atg1, and the energy-sensing kinase Snf1 are recruited to mitochondria shortly after glucose starvation. Mec1 is recruited through the adaptor protein Ggc1. Snf1 phosphorylates Mec1 on the mitochondrial surface, leading to recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 46 publications
5
69
1
4
Order By: Relevance
“…Indeed, ATM controls mitochondrial response to nuclear DNA damage (Valentin-Vega et al, 2012;Shimura et al, 2017), and contributes to the maintenance of mtDNA copy numbers in fibroblasts under normal conditions (Eaton et al, 2007). Likewise, ATR is recruited at the mitochondrial periphery to control glucose starvation-induced autophagy in yeast (Yi et al, 2017), and was shown to suppress cytochrome c release from mitochondria, thereby inhibiting apoptosis (Hilton et al, 2015). Reciprocally, the sensing of mtDNA damage can trigger the relocalization of repair-related proteins in mitochondria, including p53 (Wong et al, 2009;Boesch et al, 2011), the SOG1 functional homologue.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, ATM controls mitochondrial response to nuclear DNA damage (Valentin-Vega et al, 2012;Shimura et al, 2017), and contributes to the maintenance of mtDNA copy numbers in fibroblasts under normal conditions (Eaton et al, 2007). Likewise, ATR is recruited at the mitochondrial periphery to control glucose starvation-induced autophagy in yeast (Yi et al, 2017), and was shown to suppress cytochrome c release from mitochondria, thereby inhibiting apoptosis (Hilton et al, 2015). Reciprocally, the sensing of mtDNA damage can trigger the relocalization of repair-related proteins in mitochondria, including p53 (Wong et al, 2009;Boesch et al, 2011), the SOG1 functional homologue.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the subcellular localisation dynamics of SnRK1 itself adds to the complexity of this question. For yeast SNF1, transient complex formation at mitochondria has been described recently . Although it is accepted that the regulatory beta subunits are responsible for AKIN10 partitioning between nucleus and cytoplasm , detailed knowledge on the location of transient signalling complex formation, as has been observed in yeast, is still missing in plants.…”
Section: Discussionmentioning
confidence: 99%
“…The role of autophagy in starvation for glucose-grown cells is controversial. A few studies conclude that autophagy is neither activated nor necessary for short-term survival during starvation (12, 32); whereas, other studies suggest the opposite (8, 33). We observed that autophagy is essential for cell survival after glucose starvation within 7 days and that ATP levels depended on autophagy within the first 24h of starvation.…”
Section: Discussionmentioning
confidence: 99%